2017
DOI: 10.1038/srep42193
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic signatures of invasive status in populations of marine invertebrates

Abstract: Epigenetics, as a DNA signature that affects gene expression and enables rapid reaction of an organism to environmental changes, is likely involved in the process of biological invasions. DNA methylation is an epigenetic mechanism common to plants and animals for regulating gene expression. In this study we show, for the first time in any marine species, significant reduction of global methylation levels during the expansive phase of a pygmy mussel (Xenostrobus securis) recent invasion in Europe (two-year old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 58 publications
9
77
0
Order By: Relevance
“…As the population resides for a longer period in some area, the level of methylation increases due to accumulation of epigenetic changes. The same pattern has been observed in populations of marine invasive invertebrates (Ardura et al, ). In their study, Ardura et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As the population resides for a longer period in some area, the level of methylation increases due to accumulation of epigenetic changes. The same pattern has been observed in populations of marine invasive invertebrates (Ardura et al, ). In their study, Ardura et al .…”
Section: Discussionsupporting
confidence: 80%
“…In their study, Ardura et al . () demonstrated reduction in DNA methylation in a new population of Pygmy mussel during the expansion, while populations of older introductions showed higher levels of methylation. They obtained similar results analysing populations of the invasive Australian tubeworm.…”
Section: Discussionmentioning
confidence: 95%
“…For C. robusta and C. intestinalis , a great proportion of subepiloci was polymorphic, especially for m‐subepiloci (79.03%–92.40% in C. robusta , 81.39%–94.39% in C. intestinalis ). The ratios of polymorphic loci were higher than those in other species, such as the tubeworm F. enigmaticus where only 50% of the methylation‐susceptible loci were polymorphic (Ardura et al., ). A study on a rare floodplain herb Viola elatior showed that the polymorphism among populations ranged from 22.7% to 61.8% for u‐subepiloci and varied from 30.6% to 61.8% for methylated subepiloci (Schulz, Eckstein, & Durka, ).…”
Section: Discussionmentioning
confidence: 96%
“…Liebl, Schrey, Richards, and Martin () inferred that high methylation diversity could compensate for reduced genetic diversity during the invasion process of the house sparrow Passer domesticus . Interestingly, introduced populations of bluegrass Poa annua tended to have higher levels of methylation diversity than native populations (Chwedorzewska & Bednarek, ), and studies of the pygmy mussel ( Xenostrobus securis ) and tubeworm ( Ficopomatus enigmaticus ) found that recently introduced populations seemed to be less methylated in comparison with older introduced populations (Ardura, Zaiko, Morán, Planes, & Garcia‐Vazquez, ). Importantly, studies of invasive plants have also detected the association between DNA methylation variation and different habitats (Gao et al., ; Richards et al., ), and the authors further identified habitat‐related methylated loci (Richards et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To test the relationship between genome‐wide variation in DNA methylation and parasite loads, the proportion of methylated loci per individual was calculated as the proportion of loci scored as methylated over the total number of loci observed per individual (“0” for unmethylated and “1” for methylated, excluding the missing data cells per individual). The proportion (or percentage) of methylated loci has been previously used to analyze differences in epigenetic profiles among groups (Ardura, Zaiko, Morán, Planes, & Garcia‐Vazquez, ; Groot, Wagemaker, Ouborg, Verhoeven, & Vergeer, ; Veerger et al, ), and has shown both inter‐ and intraspecific variation (Alonso, Pérez, Bazaga, Medrano, & Herrera, ). We then employed a generalized linear model with a binomial link to model proportion of methylated loci as a function of scaled parasite load, selfing lineage, sampling site, and inbreeding status.…”
Section: Methodsmentioning
confidence: 99%